Winged bean chymotrypsin inhibitors retard growth of Helicoverpla anmigera - Telang, Manasi A.; Giri, Ashok P.; Pyati, Prashant S.; Gupta, Vidya S.; Tegeder, Mechthild; Franceschi, Vincent R. (Gene, 2009)
Two putative Kunitz-type chymotrypsin inhibitor genes (WC12 and WC15) were isolated from winged bean (Psophocarpus tetragonolobus (L.) DC). While WC12 has previously been characterized, WC15 represents a new member of the WC1 family. WC15 was exclusively expressed in winged bean seeds. Theoretical translation of both the genes resulted into polypeptides of 207 amino acids with 86% sequence similarity. The polypeptide sequences contain four half-cysteine residues and a well-conserved Leu(65)-Ser(66) reactive site, typical for chymotrypsin inhibitors. WC15 and WC12 were expressed in Pichia pastoris and the recombinant proteins were assayed against various proteinases. Both the inhibitors strongly inhibited commercially available bovine chymotrypsin. More importantly, gut proteinases of Helicoverpa armigera larvae that damage many important crop plants, were inhibited by WC12 and WC15. In addition, both proteinase inhibitors demonstrated significant reduction of growth of H. armigera larvae after feeding on inhibitor incorporated artificial diets. The inhibitory effects of WC12 and WC15 on activity of proteinases and larval growth make these proteins and their genes promising candidates for enhancing plant defense against H. armigera using transgenic plants. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Antimetabolic effect; Digestive gut proteinases; Kunitz-type proteinase inhibitor; Organ-specific mRNA expression; Psophocarpus tetragonolobus

Way toward ``dietary pesticides'': molecular investigation of insecticidal action of caffeic acid against helicoverpa armigera - Joshi, Rakesh S.; Wagh, T. P.; Sharma, N.; Mulani, Fayaj A.; Sonavane, U.; Thulasiram, H. V.; Joshi, Rakesh S.; Gupta, Vidya S.; Giri, Ashok P. (Journal of Agricultural and Food Chemistry, 2014)
Bioprospecting of natural molecules is essential to overcome serious environmental issues and pesticide resistance in insects. Here we are reporting insights into insecticidal activity of a plant natural phenol. In silico and in vitro screening of multiple molecules supported by in vivo validations suggested that caffeic acid (CA) is a potent inhibitor of Helicoverpa armigera gut proteases. Protease activity and gene expression were altered in CA-fed larvae. The structure-activity relationship of CA highlighted that all the functional groups are crucial for inhibition of protease activity. Biophysical studies and molecular dynamic simulations revealed that sequential binding of multiple CA molecules induces conformational changes in the protease(s) and thus lead to a significant decline in their activity. CA treatment significantly inhibits the insect's detoxification enzymes, thus intensifying the insecticidal effect. Our findings suggest that CA can be implicated as a potent insecticidal molecule and explored for the development of effective dietary pesticides.
Keywords: Caffeic acid; Helicoverpa armigera; insecticidal activity; protease inhibitor

WRKY1 acts as a key component improving resistance against Alternaria solani in wild tomato, Solanum arcanum Peralta - Shinde, Balkrishna A.; Dholakia, Bhushan B.; Hussain, Khalid; Aharoni, Asaph; Giri, Ashok P.; Kamble, Avinash C. (Plant Biotechnology Journal, 2018)
Early blight (EB), caused by Alternaria solani, is a major threat to global tomato production. In comparison with cultivated tomato (Solanum lycopersicum), a wild relative, S.arcanum exhibits strong resistance against EB. However, molecular cascades operating during EB resistance in wild or cultivated tomato plants are largely obscure. Here, we provide novel insight into spatio-temporal molecular events in S.arcanum against A.solani. Transcriptome and co-expression analysis presented 33-WRKYs as promising candidates of which 12 SaWRKYs displayed differential expression patterns in resistant and susceptible accessions during EB disease progression. Among these, SaWRKY1 exhibited induced expression with significant modulation in xyloglucan endotrans hydrolase 5 (XTH5) and MYB2 expressions that correlated with the disease phenotypes. Electro-mobility shift assay confirmed physical interaction of recombinant SaWRKY1 to SaXTH5 and SaMYB2 promoters. Comparative WRKY1 promoter analysis between resistant and susceptible plants revealed the presence of crucial motifs for defence mechanism exclusively in resistant accession. Additionally, many defence-related genes displayed significant expression variations in both the accessions. Further, WRKY1 overexpressing transgenic plants exhibited higher levels of EB resistance while RNAi silencing lines had increased susceptibility to A.solani with altered expression of XTH5 and MYB2. Overall, these findings demonstrate the positive influence of WRKY1 in improving EB resistance in wild tomato and this could be further utilized as a potential target through genetic engineering to augment protection against A.solani in crop plants.
Keywords: Alternaria solani; early blight; Solanum arcanum; Tomato; WRKY1; XTH5